2020
DOI: 10.3390/cells9051275
|View full text |Cite
|
Sign up to set email alerts
|

SPON1 Can Reduce Amyloid Beta and Reverse Cognitive Impairment and Memory Dysfunction in Alzheimer’s Disease Mouse Model

Abstract: Alzheimer’s disease (AD) is a complex, age-related neurodegenerative disease that is the most common form of dementia. However, the cure for AD has not yet been founded. The accumulation of amyloid beta (Aβ) is considered to be a hallmark of AD. Beta-site amyloid precursor protein cleaving enzyme 1 (BACE1), also known as beta secretase is the initiating enzyme in the amyloidogenic pathway. Blocking BACE1 could reduce the amount of Aβ, but this would also prohibit the other functions of BACE1 in brain physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Blocking BACE1 can potentially reduce the abundance in amyloid‐β, however, this may prohibit the other functions of BACE1 in psychological activities. For SPON1, using an in vivo AD mouse model, it was found that, by injecting SPON1, the amount of amyloid‐β was significantly reduced, and subsequently, the ameliorated cognitive dysfunction and memory impairment were improved, suggesting SPON1 to be a potential AD therapy target (Park et al, 2020). Interacting with APOE, human SPON1 suppresses amyloid‐β level through the APP transgene, and has an impact on working memory performance through the activation of the triangular part of the right inferior frontal gyrus (Liu et al, 2018).…”
Section: Ad Imaging Proteomics Study Revisitedmentioning
confidence: 99%
“…Blocking BACE1 can potentially reduce the abundance in amyloid‐β, however, this may prohibit the other functions of BACE1 in psychological activities. For SPON1, using an in vivo AD mouse model, it was found that, by injecting SPON1, the amount of amyloid‐β was significantly reduced, and subsequently, the ameliorated cognitive dysfunction and memory impairment were improved, suggesting SPON1 to be a potential AD therapy target (Park et al, 2020). Interacting with APOE, human SPON1 suppresses amyloid‐β level through the APP transgene, and has an impact on working memory performance through the activation of the triangular part of the right inferior frontal gyrus (Liu et al, 2018).…”
Section: Ad Imaging Proteomics Study Revisitedmentioning
confidence: 99%
“…Interestingly, the generation of kallikrein contributes to FIX activation in conditions of FXI deficiency, therefore variation in FXI may allow bypassing effects of PKa in downstream clotting 30 . SPON1 is a cell adhesion extracellular matrix protein that also exerts an inhibitory effect on the production of amyloid-β proteins due to inhibition of beta-site amyloid precursor protein cleaving enzyme 1 (BACE1), resulting in a downregulation of amyloid-β protein formation and, therefore, potentially resulting in an attenuated activation of the CAS 31 .…”
Section: Discussionmentioning
confidence: 99%
“…55 This protein has been shown to increase in CSF of presymptomatic and affected persons carrying familial AD mutations 56 as well as to reduce Aβ and reverse cognitive impairment in AD mouse model. 57 The other two proteins were EGF-containing fibulin-like extracellular matrix protein 1 (EFEMP1), a member of the fibulin family that mediates cell-cell and cell-matrix interactions 58 ;…”
Section: Discussionmentioning
confidence: 99%